1998
DOI: 10.1038/sj.onc.1202481
|View full text |Cite
|
Sign up to set email alerts
|

A novel gene, LGI1, from 10q24 is rearranged and downregulated in malignant brain tumors

Abstract: Loss of heterozygosity for 10q23 ± 26 is seen in over 80% of glioblastoma multiforme tumors. We have used a positional cloning strategy to isolate a novel gene, LGI1 (Leucine-rich gene ± Glioma Inactivated), which is rearranged as a result of the t(10;19)(q24;q13) balanced translocation in the T98G glioblastoma cell line lacking any normal chromosome 10. Rearrangement of the LGI1 gene was also detected in the A172 glioblastoma cell line and several glioblastoma tumors. These rearrangements lead to a complete a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
160
0
10

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(180 citation statements)
references
References 25 publications
10
160
0
10
Order By: Relevance
“…Although a single transmembrane domain was initially predicted in its central part [Chernova et al, 1998], the Lgi1 protein does not contain any transmembrane domain and is therefore thought to be secreted [Morante-Redolat et al, 2002;Staub et al, 2002]. This view is supported by in vitro experiments that have shown that the Lgi1 protein produced by transfected cells is secreted into the cell medium [Furlan et al, 2006;Senechal et al, 2005].…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…Although a single transmembrane domain was initially predicted in its central part [Chernova et al, 1998], the Lgi1 protein does not contain any transmembrane domain and is therefore thought to be secreted [Morante-Redolat et al, 2002;Staub et al, 2002]. This view is supported by in vitro experiments that have shown that the Lgi1 protein produced by transfected cells is secreted into the cell medium [Furlan et al, 2006;Senechal et al, 2005].…”
Section: Introductionsupporting
confidence: 57%
“…The LGI1 gene was cloned in 1998 due to its rearrangements in the T98G glioblastoma multiforme cell line, and was found to be downregulated in many malignant gliomas, suggesting a possible tumor suppressor function [Chernova et al, 1998]. However, neither point mutations affecting the LGI1 coding sequence nor differential methylation of its core promoter region could be demonstrated in these tumors, arguing against a role of LGI1 as a tumor suppressor gene [Krex et al, 2002;Piepoli et al, 2006;Somerville et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chernova et al 8 were the first to describe LGI1, upon observing that the gene was disrupted by translocation in the T98G glioblastoma multiforme (GBM) cell line and in over one-quarter of primary tumors. LGI1 expression is absent or significantly downregulated in many highgrade but not low-grade gliomas, suggesting a role for LGI1 in glial tumor progression 8,9 .…”
Section: )mentioning
confidence: 99%
“…A detailed clinical description of each family has been presented separately 2,3,7 . 8,9 . Beginning at the amino terminus (left), the protein contained a predicted signal peptide (filled arrow; positions , an N-terminal cysteine-rich LRR flanking sequence (LRRNT; residues 45-71), three LRR repeat sequences (orange boxes; residues 90-113, 114-137 and 138-161), a C-terminal cysteine-rich LRR flanking sequence (LRRCT; residues 173-222), two direct repeat sequences (Rep1 and 2; residues 226-361 and 420-549, respectively) and a putative membrane-spanning segment (yellow rectangle).…”
Section: Urlsmentioning
confidence: 99%